2006
DOI: 10.1002/jqs.1036
|View full text |Cite
|
Sign up to set email alerts
|

The taphonomy of a Middle Devensian (MIS 3) vertebrate assemblage from Lynford, Norfolk, UK, and its implications for Middle Palaeolithic subsistence strategies

Abstract: The association of a rich lithic assemblage with a Middle Devensian mammalian assemblage at Lynford was initially thought indicative of a mammoth butchery locality, a rare occurrence for a European Middle Palaeolithic open site. However, taphonomic analyses suggest that the specimens have very different depositional histories and were incorporated into a palaeochannel in several stages. Most specimens are extremely fragmentary, probably the result of extensive trampling, and signs of weathering and root-damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A rare example of Neanderthal dispersal occurred during an initial warm phase of MIS3 at Lynford, Eastern England, its organic sediments dated by OSL to 64-67 kyr ago. Mammoths were exploited, 66 and instruments in the form of small bifaces (Mousterian of Acheulean Tradition) dominate.…”
Section: Case Study: Britain and The Biotidal Zonementioning
confidence: 99%
“…A rare example of Neanderthal dispersal occurred during an initial warm phase of MIS3 at Lynford, Eastern England, its organic sediments dated by OSL to 64-67 kyr ago. Mammoths were exploited, 66 and instruments in the form of small bifaces (Mousterian of Acheulean Tradition) dominate.…”
Section: Case Study: Britain and The Biotidal Zonementioning
confidence: 99%
“…Humans, at different stages of evolution, have variously cohabited with Deinotherium, Elephas recki, Loxodonta atlantica and Loxodonta africana in Africa (Chavaillon et al, 1987;Delagnes et al, 2006;Isaac and Crader, 1981;Klein et al, 2007;Leakey, 1971), with Mammuthus meridionalis, Mammuthus trogontherii and Palaeloxodon antiquus in Western Asia and Europe (Goren-Inbar et al, 1994;Gaudzinski, 2004;Lister, 2004;Mazza et al, 2006;Palombo and Ferretti, 2005;Santonja and Pé rez-Gonzá lez, 2005;Scott, 2007;Villa, 1990;Villa et al, 2005), with Mammuthus primigenius in the open grassland biomes of glacial Eurasia (Callow and Cornford, 1986;Hoffecker, 2002;Schreve, 2006;Stuart, 2005;Vasil'ev, 2001), with Stegodon orientalis in China (Schepartz et al, 2005), with Palaeloxodon naumanni in Japan (Kondo et al, 2001), with Mammut americanum and Mammuthus columbi in North America (Grayson and Meltzer, 2002;Haynes, 1991;Surovell et al, 2005;Surovell and Waguespack, in press), with Cuvieronius as well as with Stegomastodon in South America (Bryan et al, 1978;Dillehay, 1997;Prado et al, 2005;Ranere and Ló pez, 2007). In sum, proboscideans of different genera and species were encountered in all continents except Australia.…”
Section: Human-elephant Co-existencementioning
confidence: 99%
“…However, taphonomic analysis of the vertebrate assemblage which includes also reindeer (MNI ¼ 8), horse (MNI ¼ 2) rhinoceroses (MNI ¼ 4) and some carnivores shows that the assemblage was a palimpsest. Specimens have different depositional histories with varying degrees of weathering, breakage and abrasion; evidence for direct faunal exploitation by Neanderthals cannot be unequivocally identified (Schreve, 2006). Two important sites, La Cotte (MIS 6) and Lehringen (MIS 5e) are discussed below in the section ''Hunting and killing elephants''.…”
Section: Subsistence Exploitation Of Elephants In the Lower And Middlmentioning
confidence: 99%
“…Several authors argue that finding this type of evidence is highly unlikely for various reasons. Bone preservation in a large portion of sites is too poor, weathering also deletes part of these traces, the periostium on several bones is too thick to allow stone tools modify bone surfaces, and cartilage, tendons, ligaments and the large muscle masses also do not enable frequent contact between stone tool edges and bone surfaces (Villa, 1990;Martos, 1998;Fosse, 1998;Mussi, 2005;Villa et al, 2005;Gaudzinski et al, 2005;Schreve, 2006;Mussi and Villa, 2008). Actualistic butchery observations also show that elephant butchery can be performed leaving very few traces on bones (Crader, 1983;Haynes, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, cut marks on elephant bones are a very uncommon type of taphonomic evidence. For this reason, several researchers have turned their attention to indirect types of evidence such as isotopic analyses, use wear analyses of associated stone tools or the taphonomic study of the context where the elephant bones are found to discuss the possibility of elephant consumption by hominins (Weber, 2000;Schreve, 2006;Mussi and Villa, 2008).…”
Section: Introductionmentioning
confidence: 99%